2018
DOI: 10.1053/j.jfas.2017.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Recovery After Ankle Fractures: A Systematic Review of the Psychometric Properties of Scoring Systems

Abstract: Recovery after ankle fractures places a considerable burden on patients both short and long term. Numerous tools called patient-reported outcome measures (PROMs) have been developed to measure the outcome of ankle fractures. They can assist clinicians to measure the effect, guide intervention, and assess the rate of recovery. We identified and evaluated the psychometric properties of PROMs used in the assessment of ankle fractures. In a systematic search, we examined 4 databases from inception to December 4, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…This review updates the one completed in 2016 by Ng et al [16] which assessed the psychometric properties of PROMs for ankle fractures. The current review includes four additional recently published articles and focussed on only ankle specific PROMs, whereas the previous review also included articles assessing both ankle and generic health-related quality of life PROMs.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This review updates the one completed in 2016 by Ng et al [16] which assessed the psychometric properties of PROMs for ankle fractures. The current review includes four additional recently published articles and focussed on only ankle specific PROMs, whereas the previous review also included articles assessing both ankle and generic health-related quality of life PROMs.…”
Section: Discussionmentioning
confidence: 54%
“…Using PROMs with insufficient measurement properties in randomised controlled trial is therefore a waste of resource and unethical [15]. A systematic review assessing the psychometric properties of PROMs for ankle fracture has been completed previously [16], which concluded that the Ankle Fracture Outcome of Rehabilitation Measure (A-FORM) was the most appropriate measure to use. However, considering the small number of articles included in this review, the growing incidence of ankle fractures and subsequent need for research in this area, an update is deemed timely, with a particular focus on PROMs currently and previously used in randomised controlled trials of interventions for ankle fractures.…”
Section: Introductionmentioning
confidence: 99%
“…This review highlights frequency of use of particular outcome measures over others in clinical trials of non-pharmacological interventions for ankle fracture, most notably the OMAS. Despite some evidence for the validity and reliability of the OMAS [25, 26], there is debate amongst clinicians and researchers regarding its suitability for use, particularly with regard to the lack of a formal development process and a systematic review highlighted concerns with this in particular [11]. The research group recommended the use of a newer PROM, developed in 2014 specifically for this injury, known as the Ankle Fracture Outcome of Rehabilitation Measure (A-FORM) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been an increasing trend towards the use of patient reported outcome measures (PROMs) in clinical practice and research, in a move towards value-based healthcare delivery [9, 10]. However, debate continues regarding the most appropriate outcome measure to use for adults recovering from ankle fracture [1113]. The aim of this exploratory systematic review is to identify the primary outcome measures used in published and registered clinical trials of non-pharmacological interventions for ankle fractures in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns have been raised regarding commonly used instruments such as the Foot and Ankle Ability Measure (FAAM), 9,10 the Knee Injury and Osteoarthritis Outcome Scale, 11 and the 36-Item Short-Form Health Survey. 12 Even as a computer-adapted instrument, the Patient-Reported Outcomes Measurement Information System may not distinguish healthy recreational athletes from National Collegiate Athletic Association Division I athletes. 13 Whereas these instruments can be useful in the early stages of recovery, as a patient gains function, they cease to measure improvements in health status and thereby prevent athletic trainers (ATs) from accurately assessing the effectiveness of interventions and the functional abilities of their patients.…”
mentioning
confidence: 99%